Copper alloy material with ultrahigh strength and high conductivity and preparation method thereof

By regulating the mass ratio of Ni and Sn elements and adding alloy element M, Ni3Sn2 hexagonal structure precipitation phase is formed. Combined with directional solidification, multi-stage homogenization treatment and cyclic "cold rolling-current" treatment process, the problem of Cu-Ni-Sn alloy deterioration when improving the conductive properties is solved, achieving both high-strength and high-conductivity and simplification of process.

CN119710361AActive Publication Date: 2025-03-28CENT SOUTH UNIV

Patent Information

Application Number
CN202411930881.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

While improving the conductivity, the existing Cu-Ni-Sn alloys are difficult to maintain high strength, and the processing technology is complex, the cost is high and the conductivity is low.

Method used

By regulating the mass ratio of Ni and Sn elements, the Ni3Sn2 hexagonal structure precipitation phase is formed to improve the conductivity of the alloy; at the same time, the alloy element M, such as In, replace part of the Sn atoms, reduce the formation enthalpy of the Ni3Sn2 phase, and enhance the stability of the precipitation phase. Directional solidification and multi-stage homogenization treatment processes are adopted to form columnar crystal structure and uniform microstructure; combined with cyclic "cold rolling-current" treatment and aging treatment, the ultra-refinement of the grain and uniform precipitation of the second phase are achieved.

Benefits of technology

The ultra-high strength and high conductivity of Cu-Ni-Sn alloy are achieved, simplifying the process flow, reducing costs and improving conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710361A_ABST
    Figure CN119710361A_ABST
Patent Text Reader

Abstract

The invention discloses a copper alloy material with ultrahigh strength and high conductivity and a preparation method thereof. The copper alloy material comprises, by mass, 5%-13% of Ni, 6%-14% of Sn, 40%-70% of Sn (Ni + Sn), 0.01%-0.5% of M and the balance Cu, and M is selected from at least one of In, Al, Cr, V, Mn and Fe. The preparation process comprises the following steps: carrying out multi-stage homogenization treatment on a cast ingot of a columnar crystal structure containing the components, carrying out cyclic'processing-current treatment 'on the homogenized cast ingot to obtain an ultra-fine crystal structure, and then carrying out processing-aging treatment to obtain the ultra-fine crystal structure. The copper alloy material provided by the invention not only has ultrahigh hardness and tensile strength, but also has good conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material design, and in particular to a copper alloy material having both ultra-high strength and high electrical conductivity and a preparation method thereof. Background Art

[0002] With the rapid development of modern industry, especially in high-tech industries such as computers, semiconductors, instrumentation, information and communications, high load, high reliability and long service life have become the main development direction of conductor functional devices, which makes the service conditions of alloys used in signal transmission, structural support and thermal management systems more demanding, and therefore puts forward higher requirements on the mechanical properties of materials. In view of the excellent performance of metal materials such as copper alloys, aluminum alloys, titanium alloys, magnesium alloys, etc. in the manufacture of integrated circuit lead frames, precision electronic components, connectors, etc., they have become key structural functional materials in many high-tech fields.

[0003] Improving the strength and conductivity of the alloy at the same time is one of the important issues that must be considered to achieve high performance of Cu-Ni-Sn alloy. Microalloying is one of the important means to improve the comprehensive performance of the alloy. Adding Fe, Co, Nb, V, Ti, Si, P, Zr, Zn, and B to the Cu-Ni-Sn alloy can effectively inhibit the nucleation and growth of discontinuous precipitation phases. For example, the V element can change the growth mode of the precipitation phase, promote the precipitation of the second phase and improve the alloy's resistance to softening, thereby improving the electrical conductivity of the alloy. As a typical precipitation-strengthened alloy, the amplitude modulation structure (poor Sn, rich Sn) of Cu-Ni-Sn can be gradually transformed into γ-DO through an ordered phase transformation. 22 and γ-L1 2 Ordered phase, significantly improving the mechanical properties and electrical conductivity of the alloy; but discontinuous precipitation of γ-DO 3 The phase nucleates and grows at the grain boundary, which seriously affects the mechanical properties of the alloy. Therefore, the high-level matching of the alloy composition and process becomes the key to balancing the mechanical properties and electrical conductivity of the alloy.

[0004] At present, there are many studies on the preparation and processing of Cu-Ni-Sn alloys, mainly focusing on the preparation and processing of alloys and the addition of microalloying elements. Among them, the main technical route for preparing copper-nickel-tin alloys is: melting and casting → homogenization treatment → solution treatment → cold rolling / hot rolling → aging treatment. In the field of alloy design, domestic universities and research institutes have studied microalloying, such as adding trace amounts of Fe, Si, Nb, Al, Ti, Mn, Zr, etc., and the influence mechanism of melting and casting process, hot and cold deformation and aging process on the microstructure and mechanical properties of the alloy. The document with patent number CN116287857A discloses a high-elasticity, high-strength and high-conductivity Cu-Ni-Sn alloy and its preparation method. By adding elements such as Si, Nb, Y (8-18% nickel, 6-10% tin, 0.1-1.0% silicon, 0.1-1.2% niobium, 0.02-0.5% yttrium) during the alloy composition design process, the alloy components are optimized and adjusted, thereby improving the strength of the Cu-Ni-Sn alloy, but having no effect on the conductivity of the alloy. The document with patent number CN106435260A discloses a high-strength and high-elastic CuNiSn alloy material and its preparation method. The method greatly reduces the content of elements such as Ni and Sn while adding a small amount of elements such as Co, B, V, and P (nickel 8.5-10.5%, tin 1.8-2.8%, cobalt 0.5-1.0%, boron 0.005-0.01%, vanadium 0.01-0.05%, phosphorus 0.01-0.05%). Through smelting and casting, solution annealing, milling, rough rolling, intermediate material annealing, pickling, intermediate rolling, secondary solution treatment, finishing rolling, and aging heat treatment, the conductivity of the alloy is slightly improved, but the mechanical properties such as hardness and strength are slightly reduced. The document with patent number CN118147485A discloses a high-strength and high-conductivity Cu-Ni-Sn alloy and its preparation method. This method also greatly reduces the content of elements such as Ni and Sn, and adds a small amount of elements such as Ti, Cr, Ce (0.8-1.2% nickel, 0.8-1.0% tin, 0.3-1.0% titanium, 0.2-0.5% chromium, 0.1-0.2% cerium), so as to improve the strength, hardness and conductivity of the alloy. However, the above methods all achieve their respective purposes by reducing the content of elements such as Ni and Sn or using a multi-stage deformation heat treatment process. The use of multi-stage deformation heat treatment will make the solute atoms in the alloy precipitate as much as possible in the form of a second phase to improve the mechanical properties and electrical conductivity of the alloy. However, although the significant reduction of Ni and Sn elements is beneficial to the electrical conductivity of the alloy, it will seriously affect the mechanical properties of the alloy. If the Ni content is too low, the precipitation phase generated by the alloy during the aging process will be reduced, thereby weakening the strengthening effect of the alloy. Therefore, how to simultaneously improve the mutually exclusive properties of Cu-Ni-Sn alloys, such as strength and conductivity, becomes the key to developing ultra-high strength and high conductivity Cu-Ni-Sn alloys. Summary of the invention

[0005] In view of the shortcomings of the prior art, a first object of the present invention is to provide a copper alloy material having both ultra-high strength and high electrical conductivity.

[0006] The second object of the present invention is to provide a method for preparing a copper alloy material having both ultra-high strength and high conductivity. The preparation method of the present invention is simple and controllable and suitable for industrial production.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: The present invention discloses a copper alloy material with ultra-high strength and high electrical conductivity. The copper alloy material has the following composition by mass percentage: Ni: 5-13wt.%, Sn: 6-14wt.%, and Sn: (Ni+Sn) = 40-70wt.%, M: 0.01-0.5wt.%, and the rest is Cu, wherein M is selected from at least one of In, Al, Cr, V, Mn, and Fe, and is preferably In.

[0008] The copper alloy material provided by the present invention is formed by adjusting the mass ratio of Ni and Sn elements to form Ni 3 Sn 2 ; Hexagonal Ni 3 Sn 2 The precipitated phase reduces the solute atoms in the matrix, thereby improving the electrical conductivity of the alloy; at the same time, the Ni 3 Sn 2 The phase particles can still make a great contribution to the mechanical properties of the alloy. In addition, by adding alloying elements M, Ni 3 Sn 2 Some Sn atoms in the phase reduce the Ni 3 Sn 2 The formation enthalpy of this hexagonal structure phase enables more Ni atoms to be brought out during the aging precipitation process, thereby further purifying the matrix.

[0009] In the present invention, it is very important to control the content of each component within the scope of the present invention. If the ratio of Sn: (Ni+Sn) is too small, only Ni 3 Sn, cannot form Ni 3 Sn 2 Compounds, too large to form Ni 3 Sn compounds; if too little M is added, the solute elements in the matrix cannot be fully precipitated.

[0010] In a preferred embodiment, the copper alloy material has the following composition, calculated by mass percentage: Ni: 7.5-11wt.%, Sn: 8-12.5wt.%, and Sn: (Ni+Sn) = 40-60wt.%, M: 0.01-0.3wt.%, and the rest is Cu.

[0011] Further preferably, the copper alloy material has the following composition, calculated by mass percentage: Ni: 10-11wt.%, Sn: 10-12.5wt.%, and Sn: (Ni+Sn) = 50-55wt.%, M: 0.05-0.15wt.%, and the rest is Cu.

[0012] In a preferred embodiment, the copper alloy material has a microstructure containing γ-DO 22 Ordered phase, γ-L1 2 Ordered phase, Ni 3 (Sn,M) 2 Hexagonal structure phase. Among them, Ni 3 (Sn,M) 2 Hexagonal structure phase (this phase was first discovered in Cu-Ni-Sn alloy) In the present invention, γ-DO 22 Ordered phase, γ-L1 2 The ordered phase can improve the strength, hardness and other mechanical properties of the alloy, and Ni 3 (Sn,M) 2 The hexagonal structural phase can greatly improve the electrical conductivity of the alloy material, and can also play a certain role in enhancing the mechanical properties.

[0013] The invention discloses a method for preparing a copper alloy material with both ultra-high strength and high electrical conductivity. The method comprises the following steps: preparing various metal raw materials according to a designed ratio, smelting to obtain a melt, directionally solidifying the melt to obtain an ingot with a columnar crystal structure, performing multi-stage homogenization treatment on the ingot to obtain a homogenized billet, cyclically performing processing A-current treatment on the homogenized billet to obtain a fine-grained billet, and then sequentially performing processing B and aging treatment on the fine-grained billet to obtain the copper alloy material.

[0014] The preparation method of the present invention first prepares a columnar crystal structure by directional solidification, and then performs a multi-stage homogenization treatment to eliminate dendrite segregation in the ingot; then the surface is milled to remove surface oxide scale and impurities; then a multi-pass cycle of "processing-current treatment" is performed at room temperature to refine the grains, and high-density dislocations are introduced into the ingot through processing, and current treatment is used to cause static recovery recrystallization in the high-density dislocation area of ​​the alloy material, which greatly reduces the deformation resistance introduced by the material during the processing due to dislocation entanglement and stacking, improves the deformation capacity of the material, and significantly increases the toughness of the material, and then performs a processing-aging treatment to precipitate a large number of dispersedly distributed second phase particles in the matrix, improve the purity of the matrix, and thus improve the electrical conductivity and mechanical properties of the alloy.

[0015] The inventors found that since the deformation resistance of the columnar crystal structure is much better than that of the equiaxed crystal structure obtained by conventional smelting, the ingot with columnar crystal structure is first prepared by directional solidification, followed by multi-stage homogenization treatment to dissolve the segregated atoms back to form a supersaturated solid solution, and then through multiple cycles of "processing-current treatment", the grains can be ultra-refined to the micron level or even submicron level, improving the performance of the alloy, and finally through processing + aging, the solute atoms are dispersed and precipitated in the matrix in the form of a second phase, thereby improving the performance of the alloy. The preparation method of the present invention has the characteristics of short process, high efficiency and low cost.

[0016] According to a preferred solution, various metal raw materials are mixed according to the designed proportions, smelted at 1100-1450° C., preferably 1150-1280° C. to obtain a melt, and smelted for 5-60 minutes.

[0017] In a preferred embodiment, the smelting process adopts electromagnetic stirring, and during the process of controlling the electromagnetic stirring, the magnetic field strength is 2000-5000 Gs, and the stirring time is 1-20 min.

[0018] Further preferably, after smelting to obtain the melt, the temperature is adjusted to 1150-1180°C, and after keeping warm for 3-5 minutes, electromagnetic stirring is then applied. During the electromagnetic stirring process, the magnetic field strength is controlled to be 2000-3500 Gs, and the stirring time is 5-10 minutes.

[0019] In a preferred embodiment, during the directional solidification, a water-cooled copper mold is used for cooling, and the cooling water flow rate is 200-1000 L / h. In the present invention, the melt is directionally solidified by a water-cooled copper mold having a cooling source at the bottom of the mold to obtain an ingot with a columnar crystal structure.

[0020] In a preferred embodiment, the multi-stage homogenization process is as follows: firstly heating to 550-700°C and keeping the temperature for 0.5-4h, then heating to 780-850°C and keeping the temperature for 0.5-15h.

[0021] Further preferably, the process of the multi-stage homogenization treatment is: first heating to 620-680°C and keeping warm for 0.5-2h, then heating to 780-820°C and keeping warm for 0.5-15h. Through the multi-stage homogenization treatment, the segregated atoms are dissolved back to form a supersaturated solid solution. If only a single-stage homogenization is used, the reverse segregation of Sn in the alloy cannot be uniformly eliminated, resulting in cracking during the subsequent cold deformation process, making subsequent processing impossible.

[0022] In a preferred embodiment, during the multi-stage homogenization process, the ingot is wrapped with copper foil and charcoal particles are piled on the surface. Through the above operation, the multi-stage homogenization effect is better.

[0023] In a preferred embodiment, the homogenized blank obtained by the multi-stage homogenization treatment is first milled and then circulated for cold working A-current treatment, the thickness of the milled surface is 1-3 mm, and the surface oxide scale and impurities are removed by milling.

[0024] More preferably, the processing A is selected from one of rolling, drawing, forging, rotary forging and radial forging, preferably rolling, and more preferably cold rolling.

[0025] The preferred solution is that when the homogenized blank is processed by A-current treatment in a cycle, the deformation of a single processing A is controlled to be 5-20%, and the cycle is continued until the total deformation is 50-90%. During any current treatment, the current is controlled to be 100-1000A; current density: 15-30A / mm 2 , frequency: 400~800Hz, duty cycle: 10~30%, temperature: 600~850℃.

[0026] In actual operation, if cold processing is used, after the current is applied, the blank is cooled before the next processing step is performed.

[0027] In the present invention, a homogenized billet is subjected to a multi-pass cycle of "processing A-current treatment" at room temperature, that is, a single-pass processing A is first performed, and then current treatment is applied, and then processing A and current treatment are repeated in a cycle, and after the total deformation is directly 50-90%, current treatment is applied again. High-density dislocations are introduced into the ingot through processing, and current treatment is used to cause recrystallization in the high-density dislocation area of ​​the alloy material, which greatly reduces the deformation resistance introduced by the material during the processing due to dislocation entanglement and stacking, improves the deformation capacity of the material, and significantly increases the toughness of the material. At the same time, processing A-current treatment not only makes the grains ultra-fine, but also increases the grain boundary strengthening ability, promotes the precipitation of the second phase, and further improves the overall performance.

[0028] The inventors have found that current treatment is crucial to obtaining the above-mentioned properties. If the current treatment is changed to traditional heat treatment between 600 and 850°C, the grains will be coarse and the effect of ultra-fine grains cannot be achieved. Of course, the process parameters of the current treatment need to be effectively controlled. If the current is too large, the grains will be coarse or even grow abnormally, and if the current is too small, recrystallization cannot be achieved.

[0029] Further preferred, when the homogenized blank is processed by A-current treatment in a cycle, the deformation of a single processing A is controlled to be 5-10%, and the cycle is continued until the total deformation is 50-70%. During any current treatment, the current is controlled to be 300-600A; current density: 20-25A / mm 2 , frequency: 600~800Hz, duty cycle: 20~30%, temperature: 650~800℃.

[0030] In a preferred solution, the deformation of a single pass of the processing B is 5-15%, and the total deformation is 50-95%, preferably 70-95%.

[0031] Further preferably, the processing B is selected from one of rolling, drawing, forging, rotary forging and radial forging, preferably rolling, and more preferably cold rolling.

[0032] In a preferred embodiment, the aging treatment is performed at a temperature of 300-450° C. and a holding time of 1-240 min.

[0033] If the aging treatment parameters are controlled within the above range, the second phase can be fully precipitated. However, the aging temperature and aging time need to be controlled. If the aging time is too long, γ-DO 22 Ordered phase, γ-L1 2 The ordered phase transforms into γ-DO 3 Phase (Ni 3 Sn), while Ni 3 (Sn,In) 2 The coarsening and growth of the hexagonal phase will seriously affect the performance of the alloy. 22 Ordered phase, γ-L1 2 Ordered phase, Ni 3 (Sn,In) 2 The hexagonal structure phase cannot be fully precipitated, which seriously affects the electrical conductivity of the alloy.

[0034] More preferably, the aging treatment temperature is 325-400° C., and the holding time is 15-120 min, more preferably 30-60 min.

[0035] Principles and advantages Cu-Ni-Sn alloy is a typical precipitation-strengthened alloy. Through ordered phase transformation, the amplitude modulation structure (Sn-poor, Sn-rich) of Cu-Ni-Sn alloy can be gradually transformed into γ-DO 22 and γ-L1 2 Ordered phase, significantly improving the mechanical properties and electrical conductivity of the alloy; but discontinuous precipitation of γ-DO 3 The phase nucleates and grows at the grain boundary, seriously affecting the mechanical properties of the alloy. The present invention changes the content of Ni and Sn in the alloy and changes the microstructure of the alloy. 3 Sn precipitates into Ni 3 Sn and Ni 3 Sn 2 The hexagonal precipitated phase precipitates the solute atoms dissolved in the matrix as much as possible. The addition of In atoms replaces Ni 3 Sn 2Some Sn atoms in the Ni 3 Sn 2 The formation enthalpy of the precipitated phase is increased, making the precipitated phase more stable, thereby improving the electrical conductivity and mechanical properties of the alloy.

[0036] As a new process that can improve the organization and performance of materials quickly and effectively in recent years, electric current processing technology can make metal materials undergo instantaneous high-energy non-equilibrium input by utilizing the electroplastic effect and non-electroplastic effect of electric pulses, greatly promoting the movement of metal atoms and vacancies. High-energy electric pulse processing of solid metals can control the microstructure evolution and performance of materials, including grain refinement, segregation reduction, and change of microstructure morphology. In the cyclic "processing-current" processing process, a directional electric field is applied at both ends of the processed material, and the Joule heating effect is used to cause alloys with high-density dislocations to recover and recrystallize, thereby refining the grains.

[0037] Compared with the prior art, the present invention has the following beneficial effects: 1) Compared with the prior art, the present invention does not rely on reducing the Ni and Sn contents in the alloy (sacrificing the mechanical properties of the alloy) to improve the electrical conductivity of the alloy. Instead, the present invention adjusts the mass ratio of Ni and Sn elements to form Ni 3 Sn 2 The phase reduces the solute atoms dissolved in the matrix, thereby improving the electrical conductivity of the alloy; at the same time, the Ni 3 Sn 2 The phase particles can still make a great contribution to the mechanical properties of the alloy. In addition, by adding alloying elements M, Ni 3 Sn 2 Some Sn atoms in the phase reduce the Ni 3 Sn 2 The formation enthalpy of this hexagonal structural phase enables more Ni and Sn atoms to be brought out during the aging precipitation process, thereby further purifying the matrix and improving the electrical conductivity of the alloy.

[0038] 2) The use of graded homogenization treatment replaces the traditional heat treatment, effectively shortens the homogenization time, and effectively solves the segregation and anti-segregation problems of the Sn element in the Cu-Ni-Sn alloy. At the same time, the electric pulse and cold working are combined to use high-density dislocations to recrystallize at low temperatures, which achieves ultra-fine grains of the alloy and further improves the mechanical properties of the alloy. Finally, cold working-aging treatment is performed to precipitate dispersed second phase particles in the copper alloy matrix to improve the mechanical properties of the material.

[0039] 3) The present invention designs the composition of the alloy from the perspective of forming multiple multi-phases, and then uses multi-stage homogenization and cyclic "cold working + current treatment" processes to eliminate segregation and achieve ultra-fine grains, thereby obtaining microstructure properties with ultra-high strength and high conductivity, solving the problems of complex and cumbersome existing process flows, difficult processing, high costs, and low conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is the phase type for thermodynamic calculations; Figure 2 This is the microstructure after multi-stage homogenization treatment of Example 1; it can be seen from the figure that segregation and dendrites in the alloy are completely eliminated, and a uniform Cu matrix is ​​obtained; Figure 3 This is the microstructure after the cycle of "processing-current treatment" of Example 1. From the figure, it can be seen that the grains are fine; Figure 4 Ni of Example 1 3 (Sn,In) 2 TEM image of the phase; from the image, it can be found that the precipitated phase in the alloy is rich in Ni, Sn, and In elements. Through the energy spectrum, it can be found that this precipitated phase is Ni 3 (Sn,In) 2 ; Figure 5 This is the microstructure of the single-stage homogenization treatment of Comparative Example 1. It can be found from the figure that the dendrites in the alloy are not completely eliminated and segregation exists. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the described contents.

[0042] Example 1 This embodiment provides a copper alloy material with ultra-high strength and high conductivity and a preparation method thereof, which is smelted from components in the following weight proportions: Ni: 10wt.%, Sn: 11wt.%, In: 0.1wt.%, and the rest is Cu.

[0043] The preparation process is: 1) Directional melting: put the raw materials into the corundum crucible in order from high to low melting points according to the material composition ratio, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-evacuation valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-evacuation valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4Pa, turn on the heating power and use the induction coil to induction heat the crucible. When the melt temperature reaches 1250°C, lower the temperature to 1150°C for insulation for 5 min. At the same time, turn on the electromagnetic stirring, set the magnetic field strength to 3000 Gs, and stir for 5 min before pouring it into a water-cooled copper mold to obtain an ingot.

[0044] 2) Multi-stage homogenization treatment: Wrap the cast ingot with copper foil, pile charcoal particles on the surface, and put them into a muffle furnace for homogenization treatment. The homogenization process is set to 650℃ for 2h + 800℃ for 6h. Water cooling quenching is performed immediately after homogenization treatment.

[0045] 3) Cyclic "cold rolling-current" treatment: The homogenized ingot is milled to a thickness of 2mm to remove surface oxide scale and inclusions. Due to the segregation and reverse segregation of Sn elements, the non-shrinking area at the head of the ingot needs to be removed. Then, a cyclic "cold rolling-current" treatment is carried out at room temperature. This process uses multiple passes, with a total deformation of 70% and a single cold rolling deformation of 10%. The corresponding parameters of the current treatment process are: current: 400A; current density: 22A / mm 2 , frequency: 650Hz, duty cycle: 20%, temperature: 750℃.

[0046] 4) Cold rolling aging treatment: The samples after the cyclic “cold rolling-current” treatment were cold rolled using a four-roll reversible rolling mill with a cold rolling deformation of 90%. They were then placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350 °C and the aging holding time was 30 min.

[0047] Alloy performance indicators in this implementation case: Hardness: 452HV Tensile strength: 1720MPa Electrical conductivity: 15.34%IACS.

[0048] Example 2

[0049] This embodiment provides a copper alloy material with ultra-high strength and high conductivity and a preparation method thereof, which is smelted from components in the following weight proportions: Ni: 10wt.%, Sn: 11wt.%, In: 0.1wt.%, and the rest is Cu.

[0050] The preparation process is: 5) Directional melting: according to the material composition ratio, put the raw materials into the corundum crucible in order from high to low melting points, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-vacuum valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-vacuum valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4 Pa, turn on the heating power and use the induction coil to induction heat the crucible. When the melt temperature reaches 1250°C, lower the temperature to 1150°C for insulation for 5 min. At the same time, turn on the electromagnetic stirring, set the magnetic field strength to 3000 Gs, and stir for 5 min before pouring it into a water-cooled copper mold to obtain an ingot.

[0051] 6) Multi-stage homogenization treatment: Wrap the cast ingot with copper foil, pile charcoal particles on the surface, and put them into a muffle furnace for homogenization treatment. The homogenization process is set to 650℃ for 2h + 750℃ for 10h. After the homogenization treatment, water cooling quenching is carried out immediately.

[0052] 7) Cyclic "cold rolling-current" treatment: The homogenized ingot is milled, and the thickness is controlled at 2mm to remove the surface oxide scale and inclusions. Due to the segregation and reverse segregation of the Sn element, the non-shrinking area at the head of the ingot needs to be removed. Then the cyclic "cold rolling-current" treatment is carried out at room temperature. The process adopts multiple passes, the total deformation is 70%, the single cold rolling deformation is 10%, and the corresponding parameters of the current treatment process are: current: 400A; current density: 25A / mm2, frequency: 800Hz, duty cycle: 20%, temperature: 800℃.

[0053] 8) Cold rolling aging treatment: The samples after the cyclic “cold rolling-current” treatment were cold rolled using a four-roll reversible rolling mill with a cold rolling deformation of 90%. They were then placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350 °C and the aging holding time was 30 min.

[0054] Alloy performance indicators in this implementation case: Hardness: 438HV Tensile strength: 1632MPa Electrical conductivity: 13.13%IACS.

[0055] Example 3

[0056] The present embodiment provides a copper alloy material having both ultra-high strength and high conductivity and a preparation method thereof, which is smelted from components in the following weight proportions: Ni: 7.5wt.%, Sn: 10.5wt.%, In: 0.12wt.%, and the rest is Cu.

[0057] The preparation process is: 1) Directional melting: put the raw materials into the corundum crucible in order from high to low melting points according to the material composition ratio, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-evacuation valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-evacuation valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4 Pa, turn on the heating power and use the induction coil to induction heat the crucible. When the melt temperature reaches 1250°C, lower the temperature to 1150°C for insulation for 5 min. At the same time, turn on the electromagnetic stirring, set the magnetic field strength to 3000 Gs, and stir for 5 min before pouring it into a water-cooled copper mold to obtain an ingot.

[0058] 2) Multi-stage homogenization treatment: Wrap the cast ingot with copper foil, pile charcoal particles on the surface, and put them into a muffle furnace for homogenization treatment. The homogenization process is set to 650℃ for 2h + 800℃ for 6h. Water cooling quenching is performed immediately after homogenization treatment.

[0059] 3) Cyclic "cold rolling-current" treatment: The homogenized ingot is milled to a thickness of 2mm to remove surface oxide scale and inclusions. Due to the segregation and reverse segregation of Sn elements, the non-shrinking area at the head of the ingot needs to be removed. Then, a cyclic "cold rolling-current" treatment is carried out at room temperature. This process uses multiple passes, with a total deformation of 70% and a single cold rolling deformation of 10%. The corresponding parameters of the current treatment process are: current: 400A; current density: 22A / mm 2 , frequency: 650Hz, duty cycle: 20%, temperature: 750℃.

[0060] Cold rolling aging treatment: A four-roll reversible rolling mill was used to cold roll the samples after the cyclic “cold rolling-current” treatment. The cold rolling deformation was 90%, and then the samples were placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350 °C and the aging holding time was 30 min.

[0061] Alloy performance indicators in this implementation case: Hardness: 424HV Tensile strength: 1541MPa Electrical conductivity: 13.88%IACS.

[0062] Example 4

[0063] This embodiment provides a copper alloy material with ultra-high strength and high conductivity and a preparation method thereof, which is smelted from components in the following weight proportions: Ni: 5.5wt.%, Sn: 11wt.%, In: 0.2wt.%, and the rest is Cu.

[0064] The preparation process is: 1) Directional melting: put the raw materials into the corundum crucible in order from high to low melting points according to the material composition ratio, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-evacuation valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-evacuation valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4 Pa, turn on the heating power supply, use the induction coil to induction heat the crucible, when the melt temperature reaches 1250 ° C, reduce the temperature to 1150 ° C for insulation, the insulation time is 5 min, turn on the electromagnetic stirring at the same time, set the magnetic field strength to 3000 Gs, stir for 5 min, then cast it into a water-cooled copper mold to obtain an ingot. 2) Multi-stage homogenization treatment: Wrap the cast ingot with copper foil, pile charcoal particles on the surface, and put them into a muffle furnace for homogenization treatment. The homogenization process is set to 650℃ for 2h + 820℃ for 6h. Water cooling quenching is performed immediately after homogenization treatment.

[0065] 3) Cyclic "cold rolling-current" treatment: The homogenized ingot is milled to a thickness of 2mm to remove surface oxide scale and inclusions. Due to the segregation and reverse segregation of Sn elements, the non-shrinking area at the head of the ingot needs to be removed. Then, a cyclic "cold rolling-current" treatment is carried out at room temperature. This process uses multiple passes, with a total deformation of 70% and a single cold rolling deformation of 10%. The corresponding parameters of the current treatment process are: current: 400A; current density: 23A / mm 2 , frequency: 700Hz, duty cycle: 20%, temperature: 780℃.

[0066] Cold rolling aging treatment: A four-roll reversible rolling mill was used to cold roll the samples after the cyclic “cold rolling-current” treatment. The cold rolling deformation was 90%, and then the samples were placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350 °C and the aging holding time was 30 min.

[0067] Alloy performance indicators in this implementation case: Hardness: 408HV Tensile strength: 1448MPa Electrical conductivity: 11.45%IACS.

[0068] Comparative Example 1 This comparative example adopts commercial Cu-15Ni-8Sn alloy for preparation, which is smelted by components in the following weight proportions: Ni: 15wt.%, Sn: 8wt.%, and the rest is Cu.

[0069] The preparation process is: 1) Directional melting: put the raw materials into the corundum crucible in order from high to low melting points according to the material composition ratio, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-evacuation valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-evacuation valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4 Pa, turn on the heating power and use the induction coil to induction heat the crucible. When the melt temperature reaches 1250°C, reduce the temperature to 1150°C for insulation for 5 min. At the same time, turn on the electromagnetic stirring, set the magnetic field strength to 3000 Gs, and stir for 5 min before casting.

[0070] 2) Multi-stage homogenization treatment: Wrap the cast ingot with copper foil, pile charcoal particles on the surface, and put them into a muffle furnace for homogenization treatment. The homogenization process is set to 650℃ for 2h + 800℃ for 6h. Water cooling quenching is performed immediately after homogenization treatment.

[0071] 3) Cyclic "cold rolling-current" treatment: The homogenized ingot is milled, and the thickness is controlled at 2mm to remove the surface oxide scale and inclusions. Due to the segregation and reverse segregation of the Sn element, the non-shrinking area at the head of the ingot needs to be removed. Then the cyclic "cold rolling-current" treatment is carried out at room temperature. The process adopts multiple passes, the total deformation is 70%, the single cold rolling deformation is 10%, and the corresponding parameters of the current treatment process are: current: 400A; current density: 22A / mm2, frequency: 650Hz, duty cycle: 20%, temperature: 750℃.

[0072] Cold rolling aging treatment: A four-roll reversible rolling mill was used to cold roll the samples after the cyclic “cold rolling-current” treatment. The cold rolling deformation was 90%, and then the samples were placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350 °C and the aging holding time was 30 min.

[0073] Alloy performance indicators in this implementation case: Hardness: 401HV Tensile strength: 1367MPa Electrical conductivity: 8.78%IACS.

[0074] Comparative Example 2 In this comparative example, the alloy was prepared by a conventional single-stage homogenization process, and was smelted from components in the following weight proportions: Ni: 10wt.%, Sn: 11wt.%, In: 0.1wt.%, and the remainder was Cu.

[0075] The preparation process is: 1) Directional melting: put the raw materials into the corundum crucible in order from high to low melting points according to the material composition ratio, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-evacuation valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-evacuation valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4 Pa, turn on the heating power and use the induction coil to induction heat the crucible. When the melt temperature reaches 1250°C, reduce the temperature to 1150°C for insulation for 5 min. At the same time, turn on the electromagnetic stirring, set the magnetic field strength to 3000 Gs, and stir for 5 min before casting.

[0076] 2) Traditional homogenization treatment: The cast ingot is wrapped with copper foil, charcoal particles are piled on the surface, and placed in a muffle furnace for homogenization treatment. The homogenization process is set to 800℃ for 15h. After the homogenization treatment, water cooling quenching is immediately performed.

[0077] 3) Cyclic "cold rolling-current" treatment: The homogenized ingot is milled, and the thickness is controlled at 2mm to remove the surface oxide scale and inclusions. Due to the segregation and reverse segregation of the Sn element, the non-shrinking area at the head of the ingot needs to be removed. Then the cyclic "cold rolling-current" treatment is carried out at room temperature. The process adopts multiple passes, the total deformation is 70%, the single cold rolling deformation is 10%, and the corresponding parameters of the current treatment process are: current: 400A; current density: 22A / mm2, frequency: 650Hz, duty cycle: 20%, temperature: 750℃.

[0078] 4) Cold rolling aging treatment: The samples after the cyclic “cold rolling-current” treatment were cold rolled using a four-roll reversible rolling mill with a cold rolling deformation of 90%. They were then placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350 °C and the aging holding time was 30 min.

[0079] Alloy performance indicators in this implementation case: Hardness: 422HV Tensile strength: 1545MPa Electrical conductivity: 13.44%IACS.

[0080] Comparative Example 3 In this comparative example, the cyclic "cold rolling-current" treatment process is cancelled to prepare the alloy, which is smelted from the components in the following weight proportions: Ni: 10wt.%, Sn: 11wt.%, In: 0.1wt.%, and the rest is Cu.

[0081] The preparation process is: 1) Directional melting: put the raw materials into the corundum crucible in order from high to low melting points according to the material composition ratio, close the furnace door and air inlet, open the water cooling circulation system, set the water flow rate to 400L / h, open the mechanical pump, pre-evacuation valve and vacuum gauge, and when the atmospheric pressure inside the furnace chamber drops to 10Pa, open the high vacuum valve and the front stage valve, close the pre-evacuation valve to reduce the vacuum degree in the furnace, and when the atmospheric pressure in the chamber drops to 10 -4 Pa, turn on the heating power and use the induction coil to induction heat the crucible. When the melt temperature reaches 1250°C, reduce the temperature to 1150°C for insulation for 5 min. At the same time, turn on the electromagnetic stirring, set the magnetic field strength to 3000 Gs, and stir for 5 min before casting.

[0082] 2) Multi-stage homogenization treatment: Wrap the cast ingot with copper foil, pile charcoal particles on the surface, and put them into a muffle furnace for homogenization treatment. The homogenization process is set to 650℃ for 2h + 800℃ for 6h. After the homogenization treatment, water cooling quenching is carried out immediately.

[0083] 3) Cold rolling aging treatment: The samples after the cyclic “cold rolling-current” treatment were cold rolled using a four-roll reversible rolling mill with a cold rolling deformation of 90%. They were then placed in a muffle furnace for aging treatment. During the aging treatment, charcoal was added to the furnace to reduce surface oxidation. The aging temperature was 350°C and the aging holding time was 30 min.

[0084] Alloy performance indicators in this implementation case: Hardness: 424HV Tensile strength: 1485MPa Electrical conductivity: 12.75%IACS.

Claims

1. A copper alloy material having both ultra-high strength and high electrical conductivity, characterized in that: The copper alloy material has the following composition by mass percentage: Ni: 5~13wt.%, Sn: 6~14wt.%, and Sn: (Ni+Sn) = 40~70wt.%, M: 0.01~0.5wt.%, and the rest is Cu, and the M is selected from at least one of In, Al, Cr, V, Mn, and Fe.

2. The copper alloy material having both ultra-high strength and high electrical conductivity according to claim 1, characterized in that: The copper alloy material has the following composition by mass percentage: Ni: 7.5-11wt.%, Sn: 8-12.5wt.%, and Sn: (Ni+Sn) = 40-60wt.%, M: 0.01-0.3wt.%, and the rest is Cu.

3. The copper alloy material having both ultra-high strength and high electrical conductivity according to claim 1, characterized in that: The microstructure of the copper alloy material contains γ-DO 22 Ordered phase, γ-L12 ordered phase, Ni3(Sn,M)2 hexagonal structure phase.

4. A method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to any one of claims 1 to 3, characterized in that: The metal raw materials are mixed according to the designed proportion, smelted to obtain a melt, the melt is directionally solidified to obtain an ingot with a columnar crystal structure, the ingot is subjected to multi-stage homogenization treatment to obtain a homogenized billet, the homogenized billet is cyclically processed A-current treatment to obtain a fine-grained billet, and the fine-grained billet is then sequentially processed B and aging treatment to obtain a copper alloy material.

5. The method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to claim 4, characterized in that: Mix the metal raw materials according to the designed proportion, smelt at 1100~1450℃ to obtain the melt, smelt for 1~20min, and control the vacuum degree during smelting to 10 -5 ~10 -3 Pa; The smelting process adopts electromagnetic stirring. During the process of controlling the electromagnetic stirring, the magnetic field intensity is 2000-5000 Gs and the stirring time is 1-20 min.

6. The method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to claim 4, characterized in that: During the directional solidification, a water-cooled copper mold is used for cooling, and the cooling water flow rate is 200-1000 L / h.

7. The method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to claim 4, characterized in that: The multi-stage homogenization process is as follows: firstly heating to 550-700°C and keeping the temperature for 0.5-4h, then heating to 780-850°C and keeping the temperature for 0.5-15h; During the multi-stage homogenization process, the ingot is wrapped with copper foil and charcoal particles are piled on the surface.

8. The method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to claim 4 or 7, characterized in that: The homogenized blank obtained by the multi-stage homogenization treatment is first milled and then recycled for A-current processing, and the thickness of the milled surface is 1-3 mm.

9. The method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to claim 4, characterized in that: When the homogenized blank is processed by A-current treatment in a cycle, the deformation of a single processing A is controlled to be 5~20%, and the cycle is continued until the total deformation is 50~90%. During any current treatment, the control current is 100~1000A; current density: 15~30A / mm 2 , frequency: 400~800Hz, duty cycle: 10~30%, temperature: 600~850℃.

10. The method for preparing a copper alloy material having both ultra-high strength and high electrical conductivity according to claim 4, characterized in that: The deformation of a single pass of the processing B is 5-15%, and the total deformation is 50-95%. The temperature of the aging treatment is 300-450° C., and the insulation time is 1-240 minutes.

Citation Information

Patent Citations

  • High-strength high-flexibility CuNiSn alloy material and preparation method thereof

    CN106435260A

  • High-elasticity, high-strength and high-conductivity Cu-Ni-Sn alloy and preparation method thereof

    CN116287857A

  • High-strength and high-conductivity Cu-Ni-Sn alloy and preparation method thereof

    CN118147485A

  • Watch component made from a cuproaluminium alloy.

    CH719208A2

  • Alloy material for aerospace field and manufacturing method thereof

    CN103555990A

Cited By

  • Low-power-consumption metal film vacuum gauge dynamic response optimization method and system

    CN121762107A

  • A method and system for optimizing dynamic response of a low-power metal thin film vacuum gauge

    CN121762107B

  • Thermodynamic calculation assisted design of preparation process of high-strength and high-corrosion-resistant copper alloy material

    CN122609862A

  • Thermodynamic calculation assisted design of preparation process of high-strength and high-corrosion-resistance copper alloy pipe

    CN122609862B